Effect of several new and currently available oxime cholinesterase reactivators on tabun-intoxicated rats - Karasova, Jana Zdarova; Kassa, Jiri; Jung, Young-Sik; Musilek, Kamil; Pohanka, Miroslav; Kuca, Kamil (International journal of molecular sciences, 2008)
The therapeutical efficacies of eleven oxime-based acetylcholinesterase reactivators were compared in an in vivo (rat model) study of treatment of intoxication caused by tabun. In this group there were some currently available oximes (obidoxime, trimedoxime and HI-6) and the rest were newly synthesized compounds. The best reactivation efficacy for acetylcholinesterase in blood (expressed as percent of reactivation) among the currently available oximes was observed after administration of trimedoxime (16%) and of the newly synthesized K127 (22432) (25%). The reactivation of butyrylcholinesterase in plasma was also studied; the best reactivators were trimedoxime, K117 (22435), and K127 (22432), with overall reactivation efficacies of approximately 30%. Partial protection of brain ChE against tabun inhibition was observed after administration of trimedoxime (acetylcholinesterase 20%; butyrylcholinesterase 30%) and obidoxime (acetylcholinesterase 12%; butyrylcholinesterase 16%).
Keywords: oximes; reactivators; pretreatment; Acetylcholinesterase; butyrylcholinesterase